Fine Arts Students’ Needs Analysis in the Learning of English as a Foreign Language: a Case Study - Disashi Richard, Ntumba (International Journal of Scientific Research and Management (IJSRM), 2022)
It has been shown that needs analysis is important while dealing with ESP in the teaching / learning process. This study wanted to find out and analyze the real needs of students for the sake of improving ELT at the Académie des Beaux-Arts / Kinshasa.  Thanks to the qualitative research, this study has been concentrated on the analysis of learners’ needs in the learning of English as foreign language. One hundred students of G1, G2 and G3 of plastic arts and the two instructors of the English language at the Académie des Beaux-Arts have been questionned through interviews, and also documentary sources helped to collect data. It is necessary to tackle the learners’ needs analysis in order to establish and integrate learners’ expectations on the proposal of a new content of English related to their field. The findings have shown that the majority of learners wished that visual and handling materials focused on their daily expectations such as drawings, pictures, sketches, artistic tools, conversations related to arts domain, might be incorporated in the content of their course.